Conserved oligomeric Golgi (COG) complex genes functioning in defense are expressed in root cells undergoing a defense response to a pathogenic infection and exhibit regulation my MAPKs. - Vincent P Klink (Public Library of Science (PLoS), 2021)
The conserved oligomeric Golgi (COG) complex maintains correct Golgi structure and function during retrograde trafficking. Glycine max has 2 paralogs of each COG gene, with one paralog of each gene family having a defense function to the parasitic nematode Heterodera glycines. Experiments presented here show G. max COG paralogs functioning in defense are expressed specifically in the root cells (syncytia) undergoing the defense response. The expressed defense COG gene COG7-2-b is an alternate splice variant, indicating specific COG variants are important to defense. Transcriptomic experiments examining RNA isolated from COG overexpressing and RNAi roots show some COG genes co-regulate the expression of other COG complex genes. Examining signaling events responsible for COG expression, transcriptomic experiments probing MAPK overexpressing roots show their expression influences the relative transcript abundance of COG genes as compared to controls. COG complex paralogs are shown to be found in plants that are agriculturally relevant on a world-wide scale including Manihot esculenta, Zea mays, Oryza sativa, Triticum aestivum, Hordeum vulgare, Sorghum bicolor, Brassica rapa, Elaes guineensis and Saccharum officinalis and in additional crops significant to U.S. agriculture including Beta vulgaris, Solanum tuberosum, Solanum lycopersicum and Gossypium hirsutum. The analyses provide basic information on COG complex biology, including the coregulation of some COG genes and that MAPKs functioning in defense influence their expression. Furthermore, it appears in G. max and likely other crops that some level of neofunctionalization of the duplicated genes is occurring. The analysis has identified important avenues for future research broadly in plants.